معالم الوعظ والخطابة عند الإمام ابن الجوزي The Features Of Preaching And Rhetoric Of Imam Ibn Al-jawzi - بن صفية سليمان (University of Eloued جامعة الوادي, 2023)
من أعظم وسائل الدعوة إلى الله الوعظ والخطابة بأنواعها، وقد أولاها الشرع الحكيم والعلماء الأفذاذ عناية بالغة، ومن هؤلاء الإمام ابن الجوزي، فما هي معالم الوعظ والخطابة عند ابن الجوزي، وما ضوابطها، ومصادرها، وما صفات الواعظ والخطيب؟ وتهدف الدراسة إلى بيان المعالم التي سلكها ابن الجوزي في وعظه خطابته ليحصل به الاقتداء، ولتحقيق ذلك سلكت منهجين: المنهج الاستقرائي، والتحليلي. One of the greatest means of calling to God is preaching and rhetoric of all kinds, and the wise Sharia and distinguished scholars have given them great care, and among them is Imam Ibn al-Jawzi. The study aims at clarifying the milestones that Ibn al-Jawzi followed in his preaching of his rhetoric so that he could be emulated.
Keywords: rhetoric; preaching; Ibn al-Jawzi; الخطابة; الوعظ; ابن الجوزي